Corroded TempCore® vs dual-phase steel reinforcing bars. (29th March 2021) - Caprili, Silvia; Salvatore, Walter; Valentini, Renzo
Highlights: Durability problems affect TempCore® reinforcements causing decrease of ductility. Dual-Phase steels show good mechanical properties and durability performance. Two different procedures for accelerated corrosion tests provided comparable results. Mechanical characterization is performed in reference and corroded conditions. Correlation between corrosion entity (mass loss) and residual mechanical properties is analysed. Abstract: The paper summarizes the results of an experimental test campaign on enhanced reinforcing grades provided by Dual-Phase (DP) microstructure, compared to TempCore®. The DP improvement mainly concerns durability: due to their 'mixed' microstructure, DP steels are less affected by corrosion. Accelerated corrosion tests and mechanical tests on corroded samples were performed, using two different techniques (salt-spray chamber and impressed current density). Results highlight how different corrosion procedures can affect results, even if conclusions remain the same: DP steel bars result to be less sensitive to corrosion, showing a smaller decrease in ductility compared to TempCore bars. No relevant influence is revealed on strength performance and cyclic behaviour.